2013
DOI: 10.1186/1758-5996-5-53
|View full text |Cite
|
Sign up to set email alerts
|

The long-term ingestion of a diet high in extra virgin olive oil produces obesity and insulin resistance but protects endothelial function in rats: a preliminary study

Abstract: BackgroundIt has been hypothesized that fatty acids derived from a diet high in saturated fat may negatively affect endothelial function more significantly than a diet high in unsaturated fat; nevertheless, the effects of the long-term ingestion of monounsaturated fatty acids on endothelial function have been poorly studied.MethodsTo examine the chronic effects of monounsaturated (e.g., extra virgin olive oil (EVOO)) or saturated (e.g., margarine (M)) fatty acid-rich diets on the development of insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 70 publications
1
11
0
1
Order By: Relevance
“…There was a significant gain in the rats' body and kidney weight of third group which received naringenin with cyclosporine because of antioxidant effect of naringenin that counteracts effects of cyclosporine induced oxidative stress such as the weight loss in consistent with a previous study [26], but this is in contrast with a study [27] who reported that naringenin reduces the body weight gain based on its insulin-like properties that correct many metabolic disturbances linked to the insulin resistance without any effect on the appetite. There was also a significant gain in the rats' body weight of fourth group, which received an olive oil with cyclosporine in comparison with the second group, which received cyclosporine only, and the third group, which received naringenin with cyclosporine in consistent with [28] who reported that long-term ingestion of virgin olive oil produces weight gain and insulin resistance.…”
Section: Discussionsupporting
confidence: 67%
“…There was a significant gain in the rats' body and kidney weight of third group which received naringenin with cyclosporine because of antioxidant effect of naringenin that counteracts effects of cyclosporine induced oxidative stress such as the weight loss in consistent with a previous study [26], but this is in contrast with a study [27] who reported that naringenin reduces the body weight gain based on its insulin-like properties that correct many metabolic disturbances linked to the insulin resistance without any effect on the appetite. There was also a significant gain in the rats' body weight of fourth group, which received an olive oil with cyclosporine in comparison with the second group, which received cyclosporine only, and the third group, which received naringenin with cyclosporine in consistent with [28] who reported that long-term ingestion of virgin olive oil produces weight gain and insulin resistance.…”
Section: Discussionsupporting
confidence: 67%
“…Some animal and human studies have shown that saturated fatty acid especially palmitic acid could increase the insulin resistance (Saidpour et al, 2011). A study showed that high levels of palmitic acid in the diet could increase the demand for insulin secretion (Keita, Ramírez-San Juan, Paniagua-Castro, Garduño-Siciliano, & Quevedo, 2013). Another study has shown a relationship between saturated lipid, found in palm oil, and high plasma insulin level (Marshall et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that palmitic acid, found in palm oil, impaired the function of ß-cell and also insulin sensitivity, finally resulted in insulin resistance. In contrast to palmitic acid, oleic acid found in olive oil could control the blood glucose level by optimizing insulin production in pancreas and improving body glucose uptake and use, resulted in lowering of blood glucose levels (Keita et al, 2013). A report indicated that olive oil inclusion in diet significantly reduced the fasting plasma glucose due to the presence of a beneficial compound in olive oil named Oleuropein (Al Jamal & Ibrahim, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The long-term ingestion of a diet high fat contained in EVOO results in obesity and insulin resistance but protects endothelial function in rats. 17 Mechanisms involve in increasing COX-2 levels remain unclear and need to be elucidated in rats consuming a combination of EVOO and HFD. The vascular endothelial functions and metabolic syndrome should be further studied in rats consumed a combination of EVOO and HFD.…”
Section: Discussionmentioning
confidence: 99%